1976
DOI: 10.1111/j.0954-6820.1976.tb08216.x
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Hepatic Porphyrias in Finland

Abstract: The occurrence of hepatic porphyrias --acute intermittent porphyria (AIP) and variegate porphyria (VP)-in Finland has been studied. During a period of 9 years 107 patients with AIP and 45 patients with VP were found. The prevalence of hereditary hepatic porphyrias was calculated to be 3.4per 100 OOO inhabitants. The patients belonged to 42 different families. Eighty-nine patients (59%) had had acute attacks, whereas 63 were symptomless latent cases. Precipitating factors, symptoms and excretion of porphyrins a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
2

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(25 citation statements)
references
References 28 publications
1
22
2
Order By: Relevance
“…143 It has been suggested that skin disease occurs less frequently in areas with lower levels of sun exposure. 62 South African patients do not generally comment on a seasonal variation in the intensity of their disease, whereas this has been noted in Finland. 62 …”
Section: A Skin Diseasementioning
confidence: 91%
See 2 more Smart Citations
“…143 It has been suggested that skin disease occurs less frequently in areas with lower levels of sun exposure. 62 South African patients do not generally comment on a seasonal variation in the intensity of their disease, whereas this has been noted in Finland. 62 …”
Section: A Skin Diseasementioning
confidence: 91%
“…61 Similar reductions in PBG deaminase activity have been reported in subjects with HCP. 52,60,62 The PBG deaminase deficiency is not the consequence of a co-inherited mutation and appears to be a secondary phenomenon expressed by a proportion of subjects with PPOX deficiency. Meissner et al 48 simultaneously measured the activities of PPOX and PBG deaminase in Epstein-Barr virus-transformed lymphoblasts derived from subjects with VP and normal controls.…”
Section: B Ala Synthase and Pbg Deaminase In Vpmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of AIP in Europe is 1/75 000 inhabitants; in northern Sweden 1/1000 due to a founder effect [1,4] and in Finland 3/100 000 [5]. AIP prevalence in Argentina is about 1/125 000 inhabitants [6].…”
Section: Epidemiology Datamentioning
confidence: 99%
“…The clinical features of acute hepatic porphyria include autonomic impairments such as gastrointestinal symptoms, peripheral neuropathies, psychological dysfunction, and convulsions [1][2][3]. Porphobilinogen deaminase (PBGD) deficiency was identified in patients with acute intermittent porphyria [4].…”
Section: Introductionmentioning
confidence: 99%